Cerebral small vessel disease in memory center patients with dementia with lewy bodies and Alzheimer’s disease - Bommarito Giulia; Griffa Alessandra; Michel Patrik; Hall Caroline; Salvioni Chiabotti Paolo; Pistocchi Silvia; Alemán-Gómez Yasser; Damian Daniel; Jreige Mario; Prior John O.; Dunet Vincent; Rouaud Olivier; et al. (Alzheimer’s Research & Therapy)
Abstract Introduction Cerebral small vessel disease (CSVD) is a common co-pathology in patients with dementia with Lewy bodies (DLB) and Alzheimer’s disease (AD). A comprehensive characterization of CSVD load in DLB and AD patients referred to a memory center is lacking. Methods In this retrospective study, we collected data from patients with a clinical DLB diagnosis or clinico-biological AD diagnosis, evaluated at our memory center. They were assessed for CSVD MRI features, including enlarged perivascular spaces (PVS), presence of cerebral amyloid angiopathy (CAA) and hypertensive arteriopathy (HTNA). Differences in CSVD features between AD and DLB and across clinical stages were investigated. Regression models were used to evaluate the association between (i) cerebrovascular risk factors (CVRF) and HTNA, and (ii) CSVD features and cognition as expressed by Montreal Cognitive Assessment (MoCA). Results We included 71 DLB (76.8 ± 7.4 years old, 25 females) and 71 age- and sex-matched AD patients (and 75.2 ± 5.3 years old, 27 females). Probable CAA, according to current Boston 2.0 criteria, was observed in 22.5% of DLB and 35.2% of AD patients, while any (probable + possible) CAA rate was higher in the two groups (71.8% and 91.5%, respectively). A moderate/severe HTNA was present in 45% of DLB and 28.2% of AD patients. When comparing the two groups, DLB presented with higher HTNA score (p =.012), while AD patients had higher prevalence of any CAA (p =.002). Patients with DLB had a greater PVS burden in the basal ganglia (p =.011) and centrum semiovale (p =.004) and higher number of deep microbleeds (p =.004). Certain HTNA-related features were more pronounced at dementia stage, with respect to mild cognitive impairment. No association was observed between CVRF and HTNA. Regarding the association between CSVD and cognition, only deep microbleeds count was related to MoCA in DLB patients. Discussion DLB or AD patients present with high CSVD burden and differ in terms of features and subtype. Patients with DLB present with increased HTNA, PVS load and deep microbleeds, while patients with AD present with a higher any CAA prevalence. CSVD might impact global cognition.